1984
DOI: 10.4319/lo.1984.29.3.0609
|View full text |Cite
|
Sign up to set email alerts
|

The coupling of nitrification and denitrification in two estuarine sediments1,2

Abstract: Nitrification and denitrification in estuarine sediments were measured by 15N isotopic tracer techniques at two stations in the Patuxent River estuary for April and August. A close coupling of the two processes was demonstrated directly from the evolution of labeled N, following 15NH,+ amendments during spring experiments: > 99% of the added 15NH,+ which was oxidized to r5N0,-was subsequently reduced to 15N-labeled N, during 48-h incubations, suggesting that the two reactions were occurring in close proximity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
214
0
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(231 citation statements)
references
References 15 publications
13
214
0
4
Order By: Relevance
“…Denitrification is recognised to be limited by NO 3 -supplies and hence by nitrification in coastal sediments (Jenkins and Kemp, 1984). In our study, nitrification is the main source of NO 3 -for denitrification, with an average Dn rate contribution reaching 98 % of Dt rate at 12 o C. Since Dn was statistically correlated to temperature, this result suggests that the coupling between nitrification and denitrification is thermo-dependant and consequently could be more important under summer than winter conditions in a cold salt marsh environment.…”
Section: Discussionmentioning
confidence: 99%
“…Denitrification is recognised to be limited by NO 3 -supplies and hence by nitrification in coastal sediments (Jenkins and Kemp, 1984). In our study, nitrification is the main source of NO 3 -for denitrification, with an average Dn rate contribution reaching 98 % of Dt rate at 12 o C. Since Dn was statistically correlated to temperature, this result suggests that the coupling between nitrification and denitrification is thermo-dependant and consequently could be more important under summer than winter conditions in a cold salt marsh environment.…”
Section: Discussionmentioning
confidence: 99%
“…Il permet d'une part la régénération des formes oxydées de l'azote et d'autre part, lorsqu'il est couplé à la dénitrification dans les sédiments, il favorise l'élimination d'azote du milieu (JENKINS & KEMP, 1984 ;RYSGAARD et al, 1993 ;JENSEN et al, 1996 ; entre autres). Pour bien comprendre et quantifier les flux d'azote dans ces environnements, la mesure de l'activité nitrifiante (taux d'oxydation d'ammonium et/ou de nitrites) ainsi que le dénombrement de ces micro-organismes sont des étapes obligées.…”
Section: Introductionunclassified
“…The predictive relationship between SOD and DNF is likely applicable to other low nitrate coastal systems. This is due in part to the close coupling between nitrification and DNF in coastal ecosystems, where ambient nitrate concentrations are low (Jenkins andKemp 1984, Seitzinger 1988). Seitzinger et al (2006) suggested systems with nitrate concentrations below 10 lm will have primarily coupled nitrification-denitrification, and thus the potential for a predictive relationship between DNF and SOD.…”
Section: Relationship Of Dnf and Sodmentioning
confidence: 99%